Comparative study of hematological parameters along with effect of chemotherapy and radiotherapy in different stages of breast cancer - Shrivastava, Swati; Singh, Neelima; Nigam, Akshay Kumar; Chandel, Sanjay Singh; Shrivastava, Reetika; Kumar, Sarvesh (International Journal of Research in Medical Sciences, 2016)
Background: Breast cancer is one of the most common malignancies found among women in India. Haematological parameters have been shown to predict severity, mortality and treatment follow-up in breast cancer patients. The aim of the study was to compare haematological parameters along with effect of chemotherapy and radiotherapy in different stages of breast cancer patients. Methods: Total 235 human subjects were taken in the study. Out of which 100 normal ages matched healthy subjects were considered as controls and 135 breast cancer patients subjects as cases which were further divided into their respective stages according to TNM classification. Results: Estimation of haematological parameters was done by Sysmex Automated Hematology Analyzer Kx-21. The statistical differences between cases and control were determined by using student independent sample t-test. Conclusions: We found hemoglobin level, polymorphs, lymphocytes, monocytes and RBC count were statistically reduce (p<0.05) while other parameters were non-significant as compared to control healthy subjects. We also found deranged haematological parameters in all four stages of breast cancer. The data also indicated that patients which were on combined therapies i.e. radio and chemo have more deranged and decreased levels of haematological parameters as compared to individual therapies.